Results from a new combined test of an electromagnetic liquid argon calorimeter with a hadronic scintillating-tile calorimeter - Akhmadaliev, S; Albiol, F; Amaral, P; Ambrosini, G; Amorim, A; Anderson, K; Andrieux, M; Aubert, B; Auge, E; Badaud, F; Baisin, L; Barreiro, F; et al. (2000)
A new combined test of an electromagnetic liquid argon accordion calorimeter and a hadronic scintillating-tile calorimeter was carried out at the CERN SPS. These devices are prototypes of the barrel calorimeter of the future ATLAS experiment at the LHC. The energy resolution of pions in the energy range from 10 to 300 GeV at an incident angle θ of about 12° is well described by the expression σ/E = ((41.9 ± 1.6)%/√E + (1.8 ± 0.1)%)⊕(1.8 ± 0.1)/E, where E is in GeV. The response to electrons and muons was evaluated. Shower profiles, shower leakage and the angular resolution of hadronic showers were also studied. Results are compared with those from the previous beam test.